Merawat Diri, Mengenal Emosi: Membangun Emotional Well-Being (Psikoedukasi untuk Siswa SMA Providentia) - Juniarti, Fifi (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aims to strengthen the emotional well-being of 11th-grade students through education on contributing factors, the value of healthy social interactions, and strategies for developing self-regulation. The activity was delivered in the form of psychoeducation titled